Diabetes technology: A primer highlighting the role of the pharmacist. Issue 12 (17th November 2022) - Hess, Rick; Schumacher, Christie; Whitley, Heather P.; Reece, Sara; Knezevich, Emily L.; DeLa Peña, Lea E.; Gross, Benjamin; Knezevich, Jon T.; Ginzburg, Regina; Albanese, Nicole P.; Isaacs, Diana
Abstract: The rapid advancement of technology has ushered in a new era of diabetes management, especially with regard to continuous glucose monitoring (CGM) and insulin delivery systems. Technology is changing at a fast pace and these tools can be unknown or confusing to people with diabetes. Pharmacists can play a major role in reducing barriers and facilitating shared decision‐making regarding the individualization of technology in diabetes care. The Endocrine and Metabolism PRN Research Committee solicited the PRN membership to draft an opinion paper on diabetes technology using the Identify‐Configure‐Collaborate (ICC) framework from the Association of Diabetes Care and Education Specialists. The primary goal of the opinion paper is to provide an educational primer to health care professionals interested in learning more about the emerging diabetes technology landscape and highlight the role of the pharmacist within the ICC framework.